(untitled) (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2015)
The efficiency behavior of a two-phase system composed of an Acidifier and a UASB reactor at laboratory scale was evaluated for the biological degradation of wastewater generated at the COOLESAR S.A. slaughterhouse in the city of Valledupar, Cesar (Colombia). Initially, the sludge was acclimated and then adapted first to the reactor and later to the Acidifier, after which the two-phase system consisting of the Acidifier and UASB was operated. During the study, parameters such as pH, temperature, alkalinity, VFA, TSS, VSS, and COD were analyzed to monitor the stability and organic load removal of the system. The system was evaluated at hydraulic retention times of 36, 24, 12, 9, 6, and 3 hours, obtaining removal percentages of 96.37, 91.34, 80.70, 51.41, 31.48, and 21.52%, respectively, demonstrating that the two-phase system is efficient for treating wastewater from slaughterhouses.